Associations Between Heart Rate Variability-Derived Indexes and Training Load: Repeated Measures Correlation Approach Contribution; Journal of Strength and Conditioning Research; Vol. 36, iss. 7 - Davletjyarova K. V. Kseniya Valentinovna; Vacher Ph. Philippe; Nicolas M. Michel; Kapilevich L. V. Leonid Vladimirovich; Mourot L. Laurent (2022, 2022)
Title screen